2021
DOI: 10.3233/nhsdp200084
|View full text |Cite
|
Sign up to set email alerts
|

Between Hospitality and Hostility: Public Attitudes and State Policies Toward Syrian Refugees in Turkey

Abstract: This article provides an overview of the public attitudes and state policies toward Syrian refugees in Turkey between 2011 and 2020. Turkey’s policies toward refugees and the Syrian conflict have gradually changed over the course of the last nine years (2011–2020). Turkey’s legal approach to Syrian refugees has transformed from nonrecognition to recognition and from recognition to integration. Likewise, its military strategy has grown from one of limited engagement into one of active engagement in the face of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…M. Erdoğan, 2014). Although longitudinal empirical studies that investigate Turkish citizens’ attitudes toward Syrians over time do not exist, it is known that initial attitudes that were characterized by humanitarian concerns developed into more hostile attitudes in the public space (Secen & Gurbuz, 2021). As such, previous research has shown an increase in the number of outgroup members in a country to be associated with increases in anti-immigrant attitudes (e.g., Schneider, 2008).…”
Section: Changes In Contact and Approach-avoidance Tendencies Over Timementioning
confidence: 99%
See 2 more Smart Citations
“…M. Erdoğan, 2014). Although longitudinal empirical studies that investigate Turkish citizens’ attitudes toward Syrians over time do not exist, it is known that initial attitudes that were characterized by humanitarian concerns developed into more hostile attitudes in the public space (Secen & Gurbuz, 2021). As such, previous research has shown an increase in the number of outgroup members in a country to be associated with increases in anti-immigrant attitudes (e.g., Schneider, 2008).…”
Section: Changes In Contact and Approach-avoidance Tendencies Over Timementioning
confidence: 99%
“…Following two lines of previous research which showed a developmental pattern of increase in prejudice and decrease in positive contact experiences as children reach adolescence (e.g., Wölfer et al, 2017), and considering the increasingly hostile behaviors toward refugees in Turkey (e.g., Secen & Gurbuz, 2021), we tentatively expected positive contact and approach tendencies to decrease, while we anticipated negative contact and avoidance tendencies to increase over time (H1: “increasing outgroup negativity” ).…”
Section: The Current Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Syrian refugees are largely perceived as an economic threat by city dwellers as they face increasing pressure to compete for a limited number of jobs and accept lower wages. In some urban enclaves, where internal Kurdish migrants compete for similar jobs, communal tensions have increased (Secen and Gurbuz 2021). Victory Party capitalized on the escalation of anti-migration sentiments among secular middle classes in the wake of a chronic economic decline.…”
Section: The Emergence Of Victory Partymentioning
confidence: 99%
“…There has been a persistent rise in hostility towards Syrians, fueled by increasingly racist policies and discourse in both politics and the media. The dehumanization of refugees in general, along with intergroup and interpersonal conflicts between local community members and Syrians, has further exacerbated tensions (see Duman, 2022; ICG, 2018; Secen & Gurbuz, 2021). Despite this heightened enmity, research indicates that Syrians continue to remain in Turkey (see Erdoğan, 2020) for reasons mentioned earlier.…”
Section: Introductionmentioning
confidence: 99%